Safety, liberty, and Islamist terrorism: American and European approaches to domestic counterterrorism - Schmitt, Gary James (AEI Press., 2010)
""Safety, Liberty, and Islamist Terrorism is a rare thing: a genuinely enlightening and helpful book on counterterrorism. Through a careful comparative examination of the counterterrorism practices of four European constitutional democracies (France, Germany, the United Kingdom, and Spain), it explodes the myth that U.S. counterterrorism practices are unduly aggressive or violative of global due process norms. This outstanding volume will be invaluable to counterterrorism policymakers and comparativist scholars around the world."Jack Goldsmith, professor, Harvard Law School, and author of The Terror Presidency: Law and Judgment Inside the Bush Administration" ""This is an illuminating and invaluable study, well-researched and well-written. The comparisons between American and European counterterrorism methods will surprise many. And, in the end, the study offers reason for optimism. The systemon both sides of the Atlantichas worked pretty well, protecting our rights as well as our security."Robert Kagan, senior associate, Carnegie Endowment for International Peace, and author of Of Paradise and Power: America and Europe in the New World Order" ""Subtly argued, consistently judicious, and fascinating both in its details and in the broader comparison it draws between Europe and our own situation, this is an indispensable volume for anyone seeking to understand the varying responses of open societies to the hidden dangers in their midst."Gabriel Schoenfeld, senior fellow, Hudson Institute, and author of Necessary Secrets: National Security, the Media, and the Rule of Law" ""Safety, Liberty, and Islamist Terrorism: American and European Approaches to Domestic Counterterrorism is the most thorough and useful comparative study of European and American counterterrorism regimes I have read. It offers not merely an excellent overview of the similarities and differences between contemporary Western counterterrorism approaches but a careful account of the political development of those approaches and a savvy understanding of their attractions and vulnerabilities. Those inclined to criticize European governments as uniformly soft on terrorism will find it surprising, as will those inclined to admire Europe's law enforcement£oriented terrorism regimes. This is a book that will complicate even the most sophisticated understanding of the transatlantic divide over terrorism."Benjamin Wittes, senior fellow, Brookings Institution, and author of Law and the Long War: The Fu ...